Manajemen Kesan Mahasiswa dalam Media Sosial Instagram - Irma Juliana; Nindi Laili Safitri; Muhammad Rijal Izzul Haq; Muhammad Ardiansyah (JOURNAL SAINS STUDENT RESEARCH, 2023)
At this time, with the existence of the internet, developments in the times have become more advanced with the emergence of various social media that exist today. Instagram is an application where users can upload photos or videos with captions or short descriptions. Everyone definitely wants to do their best to show themselves in order to get recognition from other people. Dramaturgical theory is an approach used to understand impression management in social life. This research uses qualitative methods by collecting data through observation, interviews and documentation. In using Instagram, students manage the impression they want to show to other people through uploads on their Instagram social media account. Female students only display positive impressions as students to build a good image of themselves to others.